2010
DOI: 10.1111/j.1574-695x.2009.00640.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling the effect of praziquantel on liver fibrosis inSchistosoma mansoni-infected patients

Abstract: An association study of a cohort of 177 Sudanese patients infected with Schistosoma mansoni [82 (46%) males and 95 (54%) females] was conducted to evaluate the factors controlling the regression of liver fibrosis 39 months after treatment with praziquantel using ultrasound evaluation. Periportal fibrosis (PPF) was regressed in 63 (35.6%) patients, while the disease progressed to higher grades in 24 (13.6%) patients. The grade of PPF did not change in 90 (50.8%) patients. The mean values of portal vein diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Another research in Ethiopia also revealed the reversibility of schistosomal periportal fibrosis after praziquantel therapy (Berhe et al 2008). Rahoud et al (2010) reported that in Sudanese patients infected with S. mansoni, 39 months after treatment with praziquantel, ultrasound evaluation showed the periportal fibrosis was regressed in 35.6% of patients, the disease progressed to higher grades in 13.6% of patients, and there were no changes in the others. The study indicated that regression, progression, and stabilization of periportal fibrosis after praziquantel therapy was controlled by gender, age, grade of fibrosis, and possibly inherited factors.…”
Section: Discussionmentioning
confidence: 96%
“…Another research in Ethiopia also revealed the reversibility of schistosomal periportal fibrosis after praziquantel therapy (Berhe et al 2008). Rahoud et al (2010) reported that in Sudanese patients infected with S. mansoni, 39 months after treatment with praziquantel, ultrasound evaluation showed the periportal fibrosis was regressed in 35.6% of patients, the disease progressed to higher grades in 13.6% of patients, and there were no changes in the others. The study indicated that regression, progression, and stabilization of periportal fibrosis after praziquantel therapy was controlled by gender, age, grade of fibrosis, and possibly inherited factors.…”
Section: Discussionmentioning
confidence: 96%
“…With respect to organ damage, many studies have tried to analyze the efficacy of varying concentrations of PZQ on organ injury [25,26]. However, little is known of its effect to the liver and kidney as a result of repeated and higher doses for treating S. haematobium among sub-Saharan subjects.…”
Section: Discussionmentioning
confidence: 99%
“…investigated the effect of PZQ treatment (using either R or S enantiomers) on multi-donor hepatocytes seeded and co-cultivated with Kupffer cells, liver endothelial cells and hepatic stellate cells until aggregation into 3D microtissue for 48h 37,38 . Microtissues kept in culture were treated with TGF-β for 7 days and PZQ enantiomers were added during these 7 days of treatment (at day 2 and day 5) at various concentrations (10,33 or 100 µM, as shown in Fig. 2A).…”
Section: Effects Of Pzq Enantiomers In a 3d Human Microtissue Hepaticmentioning
confidence: 99%